A Study of a Foreign Language Learning Result on Nouns of Grade Four Students by Using the STAD Learning Activity - Puntila Wongsason; Sompongtam, Asst.Prof.Dr. Charoenwit; koonmee, Assoc. Prof. Dr. Jaroon (JOURNAL MAHA CHULA TANI MAHACHULALONGKORNRAJAVIDYALAYA UNIVERSITY, 2023)
The research aimed to study the results of a foreign language learning on nouns of grade four students by using the STAD learning activity in light of learning achievement, English skills and satisfaction towards the learning organizing method and to compare a learning achievement before and after students’ learning. The samples were 16 grade four students of Ban Etom School affiliated to the school network 13 under the Office of Ubon Ratchathani Primary Educational Service Area 1. The samples were derived by a simple random sampling. The research instruments were 1) 5 sets of the STAD on nouns, 2) 5 lesson plans on nouns, 3) a 20-item, multiple- choice test on nouns, 4) an assessment test on English skills, 5) a questionnaire on satisfaction towards learning. Statistics used in data analysis were percentage, mean, standard deviation and t-test. The research findings were as follows. The results of the foreign language learning on nouns of grade four students through using the STAD method were as follows. Concerning the learning achievement, it was found that prior to their learning, the students had a low learning achievement averaging 9.88 (49.88%). After learning, the students had a learning achievement at a good level averaging 16.44 (82.19%). The students’ English skill evaluations following the STAD based learning were as follows. Test 1, they had a score averaging 9.25 (77.08); test 2, they had a score averaging 9.56 (79.69); test 3, they had a score averaging 9.69 (80.73); test 4, they had a score averaging 9.81 (81.77); test 5, they had a score averaging 9.88 (82.29). The students had the highest level of satisfaction towards a foreign language learning based on the STAD. A learning achievement of grade four students following the use of the STAD on nouns had a higher average than before with a statistical significance of .01.